Current Applications and Future Directions for Vascular Stents with Stem Cells in the Treatment of Intracranial Aneurysms: A Mini-Review - Chattopadhyay, Kaustav (2025)
Vascular stents and stem cells have been used in high-acuity cases for many decades, particularly in cardiology. Providing the physician with another avenue of treatment, they have had a reasonable amount of success. However, there has been very little research conducted on seeding vascular stents with stem cells when treating intracranial aneurysms. Our work aims to understand the current literature available on the viability of such stents and the future directions one should take when choosing stents seeded with stem cells. Three computerized searches in PubMed were used. Four papers met the criteria, and two were excluded. There have been some experiments where the efficacy of vascular stents seeded with different materials was tested. G/PLL-coated stents provided multiple advantages and bioactive benefits to the mesenchymal stem cells. On the other hand, SF/SDF-1 alpha also promoted similar benefits but provoked multiple unwanted inflammatory responses. G/PLL and SF/SDF-1 alpha coated stents were able to provide satisfactory results but still require more extensive research to thoroughly understand their efficacies and safety. Future directions may include researching and discovering a wider array of biocompatible materials to seed the stents.